2007
DOI: 10.1088/0957-4484/18/46/465201
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of maghemite nanoparticles on ultraviolet-induced photo-damage in human skin fibroblasts

Abstract: This study examined the optical properties of an oxidized form of maghemite (γ-Fe(2)O(3)) nanoparticles and their protective effects against the photoaging of human skin fibroblasts irradiated with ultraviolet (UV) light. Nanoparticles with diameters ranging from 8.7 to 12 nm were prepared using a chemical co-precipitation method. The nanoparticles were coated with two surfactants to obtain a water-based product. The onset of the absorption of the γ-Fe(2)O(3) nanoparticles in the UV-visible absorption spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…HaCaT cells treated with 10 and 100 μg mL −1 of S-AgNPs had 47.8% and 53.3% levels of MMP-1 secretion, respectively. Our result is in line with the previous research which showed the inhibitory effect of maghemite nanoparticles on MMP-1 secretion [33].…”
Section: Inhibitory Effect Of S-agnps On the Production Of Mmp-1 And supporting
confidence: 93%
See 1 more Smart Citation
“…HaCaT cells treated with 10 and 100 μg mL −1 of S-AgNPs had 47.8% and 53.3% levels of MMP-1 secretion, respectively. Our result is in line with the previous research which showed the inhibitory effect of maghemite nanoparticles on MMP-1 secretion [33].…”
Section: Inhibitory Effect Of S-agnps On the Production Of Mmp-1 And supporting
confidence: 93%
“…Recently, nanoparticles synthesized from the medicinal plant have been widely reported for their anti-inflammatory, anti-cancer, anti-oxidant and antimicrobial effects [11,31,32]. There are very few studies showing the effect of nanoparticles on photoaging for e.g., Lee et al [33] reported the effect of maghemite nanoparticles in protection against ultraviolet-induced photo damage in human skin fibroblasts. Solid lipid nanoparticles of N-6-furfuryl adenine has been reported for the protective effect against photoaging [34].…”
Section: Toxicity Analysis Of S-agnpsmentioning
confidence: 99%
“…XRD spectra indicated γ-Fe 2 O 3 in the iron oxide samples with the Fe 2+ : Fe 3+ ratios: 1: 1, 1: 2, 2: 3. 24 Thus, some differences were observed between the physical and optical properties of FM1, FM2, and FM3. The objectives of the study was to determine whether the initial molar ratio of Fe 2+ : Fe 3+ induces variations in the γ-Fe 2 O 3 NPs antioxidant properties.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The γ-Fe 2 O 3 NP samples were synthesized by adjusting Fe 2+ : Fe 3+ molar ratio as 1: 1, 1: 2, or 2: 3. 24 Antioxidant Effect of FM1, FM2, and FM3 Nanoparticles. The antioxidant activity of nanoparticles (10 mg/mL) was assessed by the DPPH method for insoluble solid materials, such as iron oxide particles, as described by Paul et al 37 The positive control was used as ascorbic acid (10 μg/mL) and the DPPH activity was calculated by following eq 1:…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation